ANALISIS PEMASARAN TERNAK SAPI DI KABUPATEN ACEH TENGGARA - M. Srafaga M. Srafaga; Hasnudi Hasnudi; E.H. Kardhinata E.H. Kardhinata (JURNAL AGRICA, 2018)
The study was conducted at the animal market at Perapat Hilir Village of Babussalam  District. The sample was 10 % of the total livestock population, livestock owners and traders of cattle at the livestock market. Data were collected by interviews to farmers and cattle bust measurement at the animal market. The data processed by statistical t-test to the Hypothesis 1 and Hypothesis 2, the simple correlations to the Hypothesis 3, the F-test and linear regression to Hypothesis 4, and Chi - Square test to Hypothesis 5. The results showed the significant differences between the weight of the cow according Schrool Orion at 95% confidence level, that there are differences based on the estimated selling price with the broker and measurement formulas Schrool. There are strong relationship between distance of the village with a total cost to the livestock marketing with R squared is 0.83 so that it could be interpreted that if the distance of the village increase 1 km to the animal market will total marketing expenses increased by Rp . 4320. Sale pricing by cow age, type and scat selling season is not tested quantitatively. The perception of farmers to broker decisions can be explained that the older the age of breeders , the better response to broker decisions, the higher the education breeder increasingly not good perceptions of decisions made by the broker. Keywords : cattle, decision broker, schrool